SISTEM RESERVASI ONLINE VILLA PROMAS GREENLAND GONOHARJO MENGGUNAKAN FRAMEWORK CODEIGNITER (Information Technology and Telematics, 2014)
Abstract-The villa promas greenland gonoharjo is a place who can use to spend the night or stay overnight although to doing individual or groups program. In the process of business the villa promas greenland gonoharjo still have using a manually system. Especially to processing order. The tourism which want to order the room must be come or arrive direct to the villa promas Greenland gonoharjo or by telephone.then the receptionist make a note of all order. After that, its in order to make for report every month and then giving for villa’s management. The result of the research is a system of online order base web by using a php language program and framework codeigniter. That application can help for the tourism  which want to do order room. Because of that, the process of transaction order will be faster and easy keyword: Order,Villa, Codeigniter